2009
DOI: 10.1007/s00345-009-0484-z
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil citrate and tamsulosin combination is not superior to monotherapy in treating lower urinary tract symptoms and erectile dysfunction

Abstract: Treatment with the combination of tamsulosin only and sildenafil citrate only was not superior to tamsulosin only to enhance voiding symptoms. Also, sexual function improvement was similar for both the combination and sildenafil citrate only treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…However, a recent study with 60 LUTS/BPH and ED has reported somewhat different results. This study by Tuncel et al 27 was a randomized, open-label, three-arm study on the efficacy of tamsulosin 0.4 mg and/or sildenafil 25 mg 4 days weekly and it showed that both combination therapy and tamsulosin monotherapy were associated with similar degrees of significant improvement in IPSS (40.1%, Po0.001 and 36.2%, Po0.001, respectively): they did not differ significantly from each other in this regard (P ¼ 0.206). However, although the Qmax was improved in all three groups, the combination therapy resulted in the most marked changes (42.0%, Po0.001 for the combination therapy; 26.9%, Po0.001 for sildenafil and 26.2%, Po0.001 for tamsulosin).…”
Section: Discussionmentioning
confidence: 86%
“…However, a recent study with 60 LUTS/BPH and ED has reported somewhat different results. This study by Tuncel et al 27 was a randomized, open-label, three-arm study on the efficacy of tamsulosin 0.4 mg and/or sildenafil 25 mg 4 days weekly and it showed that both combination therapy and tamsulosin monotherapy were associated with similar degrees of significant improvement in IPSS (40.1%, Po0.001 and 36.2%, Po0.001, respectively): they did not differ significantly from each other in this regard (P ¼ 0.206). However, although the Qmax was improved in all three groups, the combination therapy resulted in the most marked changes (42.0%, Po0.001 for the combination therapy; 26.9%, Po0.001 for sildenafil and 26.2%, Po0.001 for tamsulosin).…”
Section: Discussionmentioning
confidence: 86%
“…A recent study evaluated the efficacy of sildenafil citrate (25 mg, four times/week for 8 weeks), tamsulosin (0.4 mg, once daily for 8 weeks) and the combination of both regimens in 60 men presenting with BPH/LUTS. The authors found that improvements in IPSS, Q max and PVR were more pronounced in those patients who had received the combination therapy than in those who were given sildenafil citrate only [64]. Although there is some evidence that combined therapy is more effective than monotherapy with either agent to improve voiding dysfunction in men with BPH/LUTS, additional large-scale, randomized, placebo-controlled studies are needed to assess further the clinical effectiveness of combining PDE5 inhibitors and a-blockers for the treatment of BPH/ LUTS.…”
Section: Premature Ejaculationmentioning
confidence: 94%
“…Similar findings were found in the third and fourth IIEF questions. The authors concluded that combination therapy was not superior to tamsulosin only with regard to improving voiding symptoms [28]. β 3 Adrenoreceptor Agonists β 3 adrenoreceptor agonists represent an emerging treatment for detrusor overactivity.…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 98%
“…Tuncel et al [28] studied the effects of sildenafil citrate only (25 mg four times weekly), tamsulosin only (0.4 mg/ d), and combination therapy on IPSS, Q max , PVR, Sexual Health Inventory for Men (SHIM) scores, and IIEF scores. There was a significant improvement from baseline in all groups, but it was most pronounced for the combination group (combination, 16 sildenafil citrate only, 14.8±3.9 vs 18.5±4.3), although a greater change was noted in the tamsulosin only and combination groups.…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 99%